A One-Dimensional Bio-Heat Transfer Equation with Galerkin FEM in Cylindrical Living Tissue - Pandey, Hem Raj (Journal of Advanced College of Engineering and Management, 2016)
A one-dimensional steady state bio-heat transfer model of temperature distribution in cylindrical living tissue is discussed using numerical approximation technique the Galerkin Finite element method. We observe the effects of the thermal conductivity of the thermal system. The results show that the derived solution is useful to easily and accurately study the thermal behavior of the biological system, and can be extended to such applications as parameter measurement, temperature field reconstruction and clinical treatment. Journal of Advanced College of Engineering and Management, Vol. 1, 2015, pp. 45-50